Targeting the Main Protease of SARS‐CoV‐2: From the Establishment of High Throughput Screening to the Design of Tailored Inhibitors. Issue 18 (24th March 2021) - Breidenbach, Julian; Lemke, Carina; Pillaiyar, Thanigaimalai; Schäkel, Laura; Al Hamwi, Ghazl; Diett, Miriam; Gedschold, Robin; Geiger, Nina; Lopez, Vittoria; Mirza, Salahuddin; Namasivayam, Vigneshwaran; Schiedel, Anke C.; et al.
Abstract: The main protease of SARS‐CoV‐2 (M pro ), the causative agent of COVID‐19, constitutes a significant drug target. A new fluorogenic substrate was kinetically compared to an internally quenched fluorescent peptide and shown to be ideally suitable for high throughput screening with recombinantly expressed M pro . Two classes of protease inhibitors, azanitriles and pyridyl esters, were identified, optimized and subjected to in‐depth biochemical characterization. Tailored peptides equipped with the unique azanitrile warhead exhibited concomitant inhibition of M pro and cathepsin L, a protease relevant for viral cell entry. Pyridyl indole esters were analyzed by a positional scanning. Our focused approach towards M pro inhibitors proved to be superior to virtual screening. With two irreversible inhibitors, azanitrile 8 (kinac /Ki =37 500 m −1  s −1, Ki =24.0 nm ) and pyridyl ester 17 (kinac /Ki =29 100 m −1  s −1, Ki =10.0 nm ), promising drug candidates for further development have been discovered. Abstract : The main protease (M pro ) of SARS‐CoV‐2 has been recognized as a significant drug target to treat COVID‐19. The design of a new fluorogenic substrate, the recombinant expression of M pro and the development of an HTS assay were combined with a structure‐based rational approach leading to the discovery of tailored azanitriles and indole pyridyl esters as novel, outstandingly potent M pro inhibitors.